DETERMINATION OF THE ISOTOPIC COMPOSITION OF MOLYBDENUM IN THE BOTTOM SEDIMENTS OF FRESHWATER BASINS - Malinovskii D.N.; Rodyushkin I.V.; Ohlander V. (My University, 2007)
This paper presents the results of measurements of the Mo isotopic composition in the bottom sediments (BS) of freshwater basins. Mo isotopic ratios were measured using a multicollector inductively coupled plasma mass spectrometer (MC ICP MS). Efficient methods were used in this study for Mo separation from the elements of the sample matrix and correction for instrumental mass discrimination. This allowed us to achieve a high accuracy of 0.06, 0.08, and 0.14‰ (2 σ) for the measurement of 97Mo/95Mo, 98Mo/95Mo, and 100Mo/95Mo, respectively. The range of variations in Mo isotope ratios observed in the collected BS columns was ∼2.2‰ in terms of δ97Mo/95Mo. The results obtained here suggest that geochemical processes occurring during Mo migration with land water can change the isotopic composition of Mo. It is pointed out that the potential use of Mo isotopic systematics for reconstructions of redox conditions in seawater over the geologic past requires the quantification of isotopic effects of Mo accompanying its migration on land and the extent of possible variations in the isotopic composition of Mo entering the ocean.